ISO 14000 Environmental Management System In Construction: An Examination Of Its Application In Turkey - TÜRK, AHMET MURAT (Routledge Journals, Taylor & Francis Ltd, 4 Park Square, Milton Park, Abingdon Ox14 4Rn, Oxfordshire, England, 2009)
In recent years, the ISO 14000 environmental management system (EMS) prepared by the International Standards Organization (ISO) has been widely used within all sectors throughout the world. There are some methods needed in order to maintain and develop environmental performance within all sectors, including the construction sector, for the protection of sustainable development and the environment worldwide. ISO 14000 EMS originated from such need. In recent years, an increased interest has also emerged in relation to the use of EMS in the construction sector. However, despite such interest, studies about applications regarding the use of the ISO 14000 EMS by construction firms have not reached the desired level. In this article, the impact of the ISO 14000 EMS on construction firms within Turkey is being reviewed by using the questionnaire survey method. A questionnaire survey study is conducted with 68 individual construction firms, which represent the top category in Turkey and operate in national and international markets as they are members of the Turkish Contractors Association (TCA). The obtained data are analysed in accordance with the objective of the study.
Keywords: ISO 14000; Environmental Management System (EMS); Standards; Construction; Corporate Environmental Performance; China; Çevre Yönetim Sistemi; Standartlar; İnşaat; Kurumsal Çevresel Performans; Çin